Role of 18FDG PET/CT metabolic parameters in predicting hematological toxicity during chemoradiotherapy for locally advanced cervical cancer - Meng, Tianyu; Meng, Xiangxi; Xu, Xiaoxia; Li, Xiaofan; Yang, Zhi; Li, Nan (Frontiers in Oncology, 2022)
Purpose The aim of this study is to evaluate the value of 18FDG PET/CT metabolic parameters in predicting hematological toxicity (HT) during chemoradiotherapy (CRT) for locally advanced cervical cancer (LACC). Methods and materials Forty-one patients with LACC undergoing concurrent CRT were retrospectively analyzed. The correlations among age, body mass index, FIGO stage, differentiation, maximum diameter of primary lesion, parametrial invasion, lymph node metastasis, pelvic active bone marrow volume (BMACT), BMACT volume percentage (BMACT%), maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), total lesion glycolysis (TLG), and HT were analyzed using hypothesis testing and logistic regression. A p-value< 0.05 was considered significant unless otherwise specified. Results Among the 41 patients, 19 had grade 3–4 HT and 22 had grade 0–2 HT. Only SUVmax (Z = −1.961, p = 0.050) and BMACT% (χ2 = 7.769, p = 0.020) showed statistically significant difference in univariate analysis. In logistic regression, grade 3–4 HT was not associated with SUVmax. The probability of HT occurrence in<30% BMACT% was 0.071 times less than in 30%–40% BMACT% (p = 0.010, OR = 0.071, 95% CI = 0.010–0.532), and the probability of HT occurrence in >40% BMACT% was 0.148 times less than in 30%–40% BMACT% (p = 0.037, OR = 0.148, 95% CI = 0.025–0.892). Conclusion Baseline 18FDG PET/CT BMACT% could help predict the severity of HT during CRT for LACC.